Continuity and Changes in Gandang Sarunai's Music Performance in Alam Surambi Sungai Pagu Society's Socio-Cultural Activities, South Solok Regency, West Sumatra - Marzam, Marzam; WS, Hasanuddin; Indrayuda, Indrayuda; Maestro, Esy (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2023)
This article discusses the continuity and change of gandang sarunai music performances in socio-cultural activities of the Alam Surambi Sungai Pagu community, South Solok, West Sumatra. The data were derived from the results of research compiled based on qualitative methods, utilizing literature study techniques, observation, interviews, and documentation techniques. The results of the study show that there has been a change in the performance of gandang sarunai music both in terms of venue and in terms of musical aspects of gandang sarunai nowadays. While the continuity of music is maintained, even when compared to the performances of gandang sarunai music during the time of Raja Alam of Surambi Sungai Pagu led the region administratively; gandang sarunai music has been used by all levels of society in their various socio-cultural activities nowadays. In the past, gandang sarunai music was only shown by and for the King's family. Nowadays, gandang sarunai music is used not only in the royal family's environment. Most people have also used gandang sarunai music in their various socio-cultural activities.